Neonatal diseases and oxidative stress in premature infants: an integrative review - Versiéri Oliveira de Almeida; Renan Augusto Pereira; Sérgio Luís Amantéa; Cláudia Ramos Rhoden; Maurício Obal Colvero (Elsevier, 2022)
Objective: To describe the relationship of oxidative stress and antioxidant biomarkers in cord blood of premature newborns and the prognosis of diseases in the neonatal period. Sources: This study consists of an integrative review. Searches were conducted in electronic databases Scopus, PubMed, Web of Science, and Medline/Lilacs through the Virtual Library on Health Issues, using the descriptors: "premature infants", "preterm infants", "preterm birth", "preterm", "oxidative stress", "antioxidants", "infant, premature, diseases" and "cord blood". Original articles published between 2016 and 2021 in Portuguese, English, or Spanish, which analyzed oxidative stress and/or antioxidant levels through cord blood of premature newborns and evaluated clinical outcomes, were included. Summary of the findings: Of the 1,003 studies reviewed, after exclusion of duplicate articles, analysis of titles, abstracts, and full texts, 18 articles were included. 72.2% (n = 13) of analyzed studies reported a positive association between oxidative stress and the development of prematurity-related diseases; 27.7% (n = 5) showed no significant relation. Outcomes that showed a positive association were: intrauterine growth restriction, necrotizing enterocolitis, bronchopulmonary dysplasia, intraventricular hemorrhage, fetal inflammatory response syndrome, early-onset neonatal sepsis, retinopathy of prematurity, morbidity, and mortality. Conclusion: The analysis of oxidative stress and antioxidants in cord blood of premature newborns may be useful in the prognosis of some pathologies. The consequences of oxidative damage are known to be associated with increased morbidity in the short and long term. Further investigation is needed in this population in order to define normality parameters of biomarkers, clinical manifestations, diagnosis and treatment of these conditions.